Management Strategy For Goa Garba Cultural Heritage Site As A Special Interest Tourism Attraction in Gianyar Regency - Ni Wayan Sutariani; I Wayan Wiwin; I Gusti Made Widya Sena (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
Goa Garba is a historical heritage tourism site located in Pejeng Village, Gianyar Regency. This site was built in the 12th century during the reign of King Jayapangus. The site’s potential as a tourism attraction includes stone stairways, niches, the Waja spring, and a pristine natural landscape. Activities that can be undertaken at this site include meditation and melukat (a Balinese spiritual cleansing ritual). The management of Goa Garba began in 2023 under the Gianyar Regency Tourism Office in collaboration with the local customary village (Desa Adat). This management effort aims to preserve historical heritage while enhancing the local community’s economy. However, the development of the Goa Garba Tourism Attraction (DTW Goa Garba) faces several challenges, including relatively low tourist visits compared to other destinations. Although the Tourism Office has carried out promotional and branding efforts, these have yet to significantly increase visitor interest. This issue prompted the authors to conduct an in-depth study. The objectives of this research are to describe the potential of the Goa Garba Cultural Heritage Site, analyze its strengths, weaknesses, opportunities, and threats, and formulate management strategies for its development. The research uses both qualitative and quantitative data. Data were collected through observation, interviews, and documentation, and analyzed using qualitative descriptive techniques. The findings are as follows: First, Goa Garba's tourism potential consists of natural, cultural, and limited artificial elements. The natural potential includes forested areas, a waterfall in front of the niche, and the Pakerisan River. Artificial tourism development is limited since Goa Garba focuses on special interest tourism, particularly wellness tourism. Cultural tourism potentials include the stone staircase, ancient gateway, Goa Garba cave, and niches. One of the main strengths of DTW Goa Garba lies in its historical value, particularly the footprint of Kebo Iwa found on one of the stone steps. Financial constraints are a key weakness, as they hinder the ability to repair damaged facilities. Nevertheless, Goa Garba holds potential as a unique and unspoiled site and has the opportunity to collaborate with yoga companies. Based on SWOT analysis, the position of Goa Garba falls in Quadrant II,